Micropore-mesopore double-pore composite catalyst, preparation method thereof and application of micropore-mesopore double-pore composite catalyst in direct catalytic cracking reaction of waste plastics
Through the micropore-mesoporous double-pore composite catalyst in the direct catalytic cracking reaction of waste plastics, the problem of insufficient low-carbon olefin content in waste plastic recycling is solved, and the efficient production of low-carbon olefins is achieved, with good economic benefits and operability.
Patent Information
- Application Number
- CN202310679270.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-06-08
AI Technical Summary
In the prior art, the low-carbon olefin content is relatively small in chemical recycling and utilization of waste plastics, making it difficult to effectively produce high-quality chemical raw materials.
Microporous-mesoporous double-pore composite catalyst, including ZRP-5 molecular sieve and HMS all-silicon mesoporous molecular sieve, were prepared by ball milling, beating and calcining treatment, and used for direct catalytic cracking reaction of waste plastics to generate low-carbon olefins.
It improves the conversion rate of waste plastics and low carbon olefin yield, and achieves efficient production of important chemical raw materials. The process conditions are mild, easy to operate and has good economic benefits.
Smart Images

Figure CN119114137A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst preparation and polymer material recycling, and in particular to a microporous-mesoporous double-porous composite catalyst and a preparation method thereof, as well as an application in direct catalytic cracking reactions of waste plastics. Background Art
[0002] Plastic products are widely used in various fields around the world. However, plastics are difficult to degrade naturally. If conventional landfill technology is used, although it requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. If incineration technology is used, although it can achieve the reduction requirements and recover some energy at the same time, this process is likely to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.
[0003] In the prior art, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900°C. If a catalyst is added during the thermal cracking process, it is a catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic modification method is an improvement on the catalytic cracking method. After the waste plastic is thermally cracked, a catalyst is used to catalytically modify the cracking gas. This method has higher product quality, more flexible operation and lower operating costs than the thermal cracking method and the catalytic cracking method, but the process is more complicated.
[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastics treatment technologies with broad application prospects. In the existing technology, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins is required, a two-stage method of thermal cracking-catalytic reforming is required.
[0005] Therefore, exploring a new chemical recycling process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention
[0006] The purpose of the present invention is to provide a microporous-mesoporous bi-porous composite catalyst and a preparation method thereof as well as an application in a direct catalytic cracking reaction of waste plastics in order to address the defect problem of low content of light olefins recovered in the current chemical recycling of waste plastics. The microporous-mesoporous bi-porous composite catalyst is applied to the direct catalytic cracking reaction of waste plastics to produce light olefins, thereby solving the problem of recycling waste plastics and increasing the production of light olefins, which are important chemical raw materials.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a microporous-mesoporous dual-pore composite catalyst, wherein the microporous-mesoporous dual-pore composite catalyst comprises a ZRP-5 molecular sieve and a HMS all-silicon mesoporous molecular sieve, and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, the micropore size is 0.3-0.6nm, and the mesopore size is 2-5nm;
[0008] Based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 20-50% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 50-80% by weight.
[0009] The second aspect of the present invention provides a method for preparing a microporous-mesoporous dual-porous composite catalyst, wherein the preparation method comprises:
[0010] (I) ball-milling the ZRP-5 molecular sieve to obtain the ball-milled ZRP-5 molecular sieve;
[0011] (II) mixing the HMS all-silica mesoporous molecular sieve and water to obtain the HMS all-silica mesoporous molecular sieve slurry;
[0012] (III) contacting the ball-milled ZRP-5 molecular sieve and the HMS all-silica mesoporous molecular sieve slurry and performing a slurry treatment to obtain a microporous-mesoporous dual-porous composite catalyst slurry;
[0013] (IV) The microporous-mesoporous dual-porous composite catalyst slurry is filtered, dried and calcined to obtain a microporous-mesoporous dual-porous composite catalyst.
[0014] The third aspect of the present invention provides a microporous-mesoporous biporous composite catalyst prepared by the aforementioned preparation method.
[0015] A fourth aspect of the present invention provides an application of the aforementioned microporous-mesoporous dual-porous composite catalyst in the direct catalytic cracking of waste plastics to produce light olefins.
[0016] Through the above technical solution, the technical solution of the present invention has the following advantages:
[0017] (1) The raw materials of the microporous-mesoporous dual-porous composite catalyst provided by the present invention are easily available, the preparation method is simple, the conditions are easy to control, and the product has good reproducibility.
[0018] (2) The microporous-mesoporous dual-porous composite catalyst provided by the present invention includes both a ZRP-5 molecular sieve with a certain acidity on the surface and a HMS all-silicon mesoporous molecular sieve with a larger pore size, and has a stable structure and good high temperature resistance. During the cracking reaction, the acidic sites of the microporous molecular sieve serve as the cracking active centers of the waste plastic molecules, and the mesoporous channels facilitate the diffusion of the raw material and product molecules.
[0019] (3) The microporous-mesoporous bi-porous composite catalyst provided by the present invention can convert waste plastics into light olefins in one step when used for direct catalytic cracking of waste plastics to produce light olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of light olefins, an important chemical raw material, and has good economic benefits.
[0020] (4) When the microporous-mesoporous dual-porous composite catalyst provided by the present invention is used for the direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.
[0021] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention, but do not constitute a limitation of the present invention.
[0023] Figure 1 is a small-angle X-ray diffraction (XRD) spectrum of the microporous-mesoporous dual-porous composite catalyst A of Example 1;
[0024] Figure 2 is a wide-angle X-ray diffraction (XRD) spectrum of the microporous-mesoporous dual-porous composite catalyst A of Example 1;
[0025] Figure 3 This is the pore size distribution diagram of the microporous-mesoporous dual-porous composite catalyst A of Example 1. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] As mentioned above, the first aspect of the present invention provides a microporous-mesoporous dual-pore composite catalyst, wherein the microporous-mesoporous dual-pore composite catalyst comprises a ZRP-5 molecular sieve and a HMS all-silicon mesoporous molecular sieve, and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, the micropore size is 0.3-0.6nm, and the mesopore size is 2-5nm;
[0028] Based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 20-50% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 50-80% by weight.
[0029] The inventors of the present invention have found that in the prior art, there is no process for directly catalytically cracking waste plastics to produce low-carbon olefins (including ethylene, propylene, and butene). The microporous-mesoporous dual-porous composite catalyst developed by the inventors of the present invention can solve this problem.
[0030] On the one hand, the inventors of the present invention have found that the catalyst used for the catalytic cracking of waste plastics to directly prepare light olefins should have a certain acidity and good hydrothermal stability. The ZRP-5 molecular sieve, which has a stable MFI-type topological framework structure and mild acidity, is very suitable as the main component of the waste plastic cracking catalyst. However, because the ZRP-5 molecular sieve has a small pore size (average pore size of about 0.5nm) and a small pore volume (about 0.2cm 3 / g), while the molecular weight of waste plastic products is relatively large and the molecular chain is relatively long. In the cracking reaction of waste plastic products, it is difficult for the larger reactant molecules and product molecules to diffuse between narrow channels, which not only affects the contact between the reactants and the active centers, but also easily leads to side reactions such as deep dehydrogenation, which in turn leads to a decrease in catalyst performance. Compared with microporous molecular sieves, HMS all-silica mesoporous molecular sieve materials have larger pore sizes (pore diameters are approximately 6-10 times the pore size of ZRP-5 molecular sieves) and larger pore volumes (can reach 0.8cm 3 / g or more), which is very suitable for catalytic reactions involving macromolecules. However, HMS all-silicon mesoporous molecular sieve is an all-silicon material with extremely weak surface acidity. When used alone as a catalyst to catalyze the cracking reaction of waste plastics, its activity is poor and its catalytic efficiency is not high. The inventors of the present invention found during the development and research of waste plastic cracking catalysts that if the pore advantages of HMS all-silicon mesoporous molecular sieve and the suitable surface acid centers of ZRP-5 microporous molecular sieve are comprehensively utilized, the specific surface area and pore volume of the catalyst can be effectively improved, and the internal diffusion performance in the reaction can be significantly improved. When used as a cracking catalyst in the catalytic conversion reaction of waste plastics, it can not only effectively improve the activity of the cracking catalyst, but also increase the selectivity of light olefins.
[0031] On the other hand, the inventors of the present invention have found that if the ZRP-5 molecular sieve is simply mixed with the HMS all-silicon mesoporous molecular sieve, it is difficult to give full play to the catalytic ability of the surface acidic center of the microporous molecular sieve ZRP-5 and the pore structure advantages of the HMS all-silicon mesoporous molecular sieve. In the preparation process of the cracking catalyst, if the ZRP-5 molecular sieve powder after ball milling is added to the HMS all-silicon mesoporous molecular sieve slurry, the two molecular sieves are evenly mixed by beating, and then the mixed slurry is filtered, dried and calcined to remove the template of the HMS all-silicon mesoporous molecular sieve. The microporous-mesoporous dual-porous composite catalyst obtained by this preparation method has high catalytic activity and high selectivity for low-carbon olefins in the catalytic cracking reaction of waste plastics.
[0032] According to the present invention, the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, with the micropore size being 0.4-0.5nm and the mesopore size being 3-4nm; preferably, the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, with the micropore size being 0.43-0.47nm and the mesopore size being 3.2-3.8nm.
[0033] According to the present invention, preferably, based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 25-45% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 55-75% by weight; preferably, based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 30-40% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 60-70% by weight. In the present invention, the use of the aforementioned specific content of each component can make the prepared microporous-mesoporous dual-porous composite catalyst have better catalytic activity and higher selectivity for light olefins when used for direct catalytic cracking of waste plastics to prepare light olefins.
[0034] According to the present invention, the SiO 2 / Al 2 O 3 The molar ratio is 70-300.
[0035] According to the present invention, the ZRP-5 molecular sieve is selected from one or more of ZRP-5A molecular sieve, ZRP-5B molecular sieve and ZRP-5C molecular sieve. In the present invention, the ZRP-5 molecular sieve can be obtained by commercial means. Specifically, the ZRP-5 molecular sieve is more preferably: SiO 2 / Al 2 O 3 ZRP-5A molecular sieve with a molar ratio of 70; SiO 2 / Al 2 O 3 ZRP-5B molecular sieve with a molar ratio of 100; SiO2 / Al 2 O 3 The ZRP-5C molecular sieve has a molar ratio of 300. The above three molecular sieves were purchased from Wuhan Hezhong Biochemical Manufacturing Co., Ltd.
[0036] According to the present invention, the specific surface area of the microporous-mesoporous dual-pore composite catalyst is 650-800m 2 / g, pore volume is 0.58-0.79ml / g; preferably, the specific surface area of the microporous-mesoporous dual-pore composite catalyst is 690-780m 2 / g, and the pore volume is 0.62-0.75 ml / g; more preferably, the specific surface area of the microporous-mesoporous dual-pore composite catalyst is 725-776 m 2 / g, and the pore volume is 0.66-0.72 ml / g. In the present invention, the microporous-mesoporous dual-pore composite catalyst has the above structural parameters, and has better catalytic activity and higher selectivity for light olefins when used for direct catalytic cracking of waste plastics to prepare light olefins.
[0037] The second aspect of the present invention provides a method for preparing a microporous-mesoporous dual-porous composite catalyst, wherein the preparation method comprises:
[0038] (I) ball-milling the ZRP-5 molecular sieve to obtain the ball-milled ZRP-5 molecular sieve;
[0039] (II) mixing HMS all-silica mesoporous molecular sieve raw powder and water to obtain HMS all-silica mesoporous molecular sieve raw slurry;
[0040] (III) contacting the ball-milled ZRP-5 molecular sieve and the HMS all-silica mesoporous molecular sieve slurry and performing a slurry treatment to obtain a microporous-mesoporous dual-porous composite catalyst slurry;
[0041] (IV) The microporous-mesoporous dual-porous composite catalyst slurry is filtered, dried and calcined to obtain a microporous-mesoporous dual-porous composite catalyst.
[0042] According to the present invention, in step (I), the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600r / min, preferably 300-500r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.
[0043] According to the present invention, after washing the HMS all-silica mesoporous molecular sieve prepared above, a certain amount of distilled water is added to obtain the HMS all-silica mesoporous molecular sieve slurry.
[0044] According to the present invention, the weight ratio of the ZRP-5 molecular sieve to the HMS all-silicon mesoporous molecular sieve slurry is 1: (20-250), preferably 1: (50-180). In the present invention, it should be noted that the HMS all-silicon mesoporous molecular sieve slurry contains not only water, but also a template used in the preparation of the mesoporous molecular sieve. Both the template and water are removed by calcination in the last step of the preparation of the microporous-mesoporous dual-porous composite catalyst.
[0045] According to the present invention, in step (III), the slurrying process may include: adding ZRP-5 molecular sieve powder to HMS all-silicon mesoporous molecular sieve slurry, and rapidly stirring with a stirring paddle. The stirring speed may be greater than or equal to 100 rpm, preferably greater than or equal to 300 rpm; the stirring time may be 1-24h, preferably 5-12h.
[0046] According to the present invention, in step (IV), the filtration process has no special requirements and can be a filtration method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtration process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.
[0047] According to the present invention, in step (IV), the drying conditions include: temperature of 50-150° C., preferably 60-120° C.; time of 1-24 h, preferably 3-16 h.
[0048] According to the present invention, in step (IV), the calcination conditions include: temperature of 450-700° C., preferably 500-650° C.; time of 4-30 h, preferably 6-20 h.
[0049] According to the present invention, the method for preparing the HMS all-silicon mesoporous molecular sieve raw powder comprises:
[0050] (1) mixing and contacting a template, an alcohol and water under hydrolysis gel making conditions to obtain a mixture; wherein the template is a neutral surfactant;
[0051] (2) adding a silicon source dropwise to the mixture to obtain a gel mixture;
[0052] (3) crystallizing the gel mixture; and then filtering and washing the crystallized product to obtain HMS all-silica mesoporous molecular sieve raw powder.
[0053] According to the present invention, in step (1), preferably, the template is selected from one or more of dodecylamine, tetradecylamine, hexadecylamine and octadecylamine.
[0054] According to the present invention, in step (1), the alcohol is ethanol.
[0055] According to the present invention, in step (1), the silicon source is a silicon-containing organic compound and / or a silicon-containing inorganic compound; preferably a silicon-containing organic compound; more preferably one or more of ethyl orthosilicate, methyl orthosilicate and butyl orthosilicate.
[0056] According to the present invention, in step (1), the weight ratio of the template, the alcohol, the water and the silicon source is 1: (1-30): (2-20): (1-12); preferably 1: (3-15): (4-10): (2-8).
[0057] According to the present invention, in step (1), the contacting conditions include: temperature of 10-80°C, preferably 20-60°C; time of 0.5-5h, preferably 1-3h. Preferably, in order to make the template, ethanol, water and silicon source mix evenly, the contacting process can be carried out under stirring.
[0058] According to the present invention, in step (1), the crystallization conditions include: temperature of 10-80°C, preferably 20-60°C; time of 3-48h, preferably 5-30h.
[0059] According to the present invention, in step (1), the washing process may include: obtaining a solid product after filtering, repeatedly washing the solid product with distilled water or ethanol (the number of washing times may be 5-10 times), and then filtering with suction.
[0060] The third aspect of the present invention provides a microporous-mesoporous biporous composite catalyst prepared by the aforementioned preparation method.
[0061] A fourth aspect of the present invention provides an application of the aforementioned microporous-mesoporous dual-porous composite catalyst in the direct catalytic cracking of waste plastics to produce light olefins.
[0062] According to the present invention, the waste plastic is waste polyethylene plastic (polyethylene waste plastic).
[0063] According to the present invention, the application method of the catalyst comprises: under specific conditions, waste polyethylene plastic particles are contacted with a microporous-mesoporous biporous composite catalyst.
[0064] In the present invention, the conditions for contacting the waste polyethylene plastic particles with the microporous-mesoporous biporous composite catalyst include: the contact temperature can be 420-580°C, preferably 450-540°C; the contact pressure can be 0.01-1.0Mpa, preferably 0.05-0.5Mpa; the contact time can be 0.5-12h, preferably 1-5h; the weight ratio of the microporous-mesoporous biporous composite catalyst to the waste polyethylene plastic particles can be 1:0.5-50, preferably 1:2-30.
[0065] The present invention will be described in detail below through examples.
[0066] In the following examples and comparative examples:
[0067] (1) The small-angle XRD test of the samples was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS, Germany, with a scanning range of 0.5-10°.
[0068] (2) The wide-angle XRD test of the samples was carried out on an X'Pert MPD X-ray powder diffractometer produced by Philips of the Netherlands, using a Cu Kα target and a scanning range of 2θ=5-90°.
[0069] (3) The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA. The samples were vacuum degassed at 350°C for 4 hours before measurement. The specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0070] (4) The SEM images of the samples were obtained using an XL-30 field emission environmental scanning electron microscope produced by FEI Company, USA.
[0071] (5) The elemental analysis experiment of the samples was carried out on an Eagle III energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.
[0072] (6) The drying oven was manufactured by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0073] (7) The muffle furnace is manufactured by CARBOLITE, model CWF1100.
[0074] (8) Other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.
[0075] Example 1
[0076] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0077] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0078] Dissolve 10.0g of dodecylamine in a mixed solution of 72.0g of ethanol and 63.0g of distilled water, heat to 40°C, stir for 30 minutes, and then add 42.0g of tetraethyl orthosilicate (TEOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 2h. After the addition is complete, continue stirring and crystallizing at 40°C for 20 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product 8 times with anhydrous ethanol, filter, add an appropriate amount of distilled water, and obtain 400g of HMS mesoporous molecular sieve slurry A.
[0079] 50 g ZRP-5B molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 100 and the specific surface area is 342m 2 / g, pore volume 0.18cm 3 / g) was added into a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 60°C, the rotation speed of the grinding balls was 400r / min, and the ball milling time was 16h. 6.2g of the ZRP-5B molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for beating, the stirring speed was 500 rpm, and the beating time was 10h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 90°C for 5 hours and calcined at 600°C for 12 hours to obtain a microporous-mesoporous bi-porous composite catalyst A.
[0080] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst A, the content of the ZRP-5 molecular sieve is 36% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 64% by weight.
[0081] The specific surface area of the microporous-mesoporous dual-pore composite catalyst A is 776 m 2 / g, pore volume 0.72cm 3 / g.
[0082] Figure 1 is the small-angle XRD spectrum of catalyst A. Figure 1 It can be seen that Figure 1A broad single diffraction peak appeared in the sample, with a peak value between 2θ=2-3°, which is a characteristic diffraction peak of the (100) crystal plane. This shows that the sample has a typical hexagonal worm-like pore structure. This shows that after the microporous-mesoporous dual-pore composite catalyst A was calcined at 600°C, the HMS mesoporous molecular sieve crystal phase did not change significantly, and still maintained a typical hexagonal mesoporous structure.
[0083] Figure 2 This is the wide-angle XRD spectrum of catalyst A. Figure 2 The spectrum shows that the x-ray diffraction angles of the sample are mainly: 2θ = 7.8°, 8.9°, 14.9°, 23.1° and 24.0°. These five diffraction signals are consistent with the diffraction spectrum of ZRP-5 molecular sieve, indicating that the ZRP-5 molecular sieve in catalyst A still maintains a typical MFI crystal phase structure, and the ball milling, slurrying and calcination processes in the catalyst preparation do not destroy the basic structure of ZRP-5 molecular sieve.
[0084] Figure 3 is the pore size distribution diagram of catalyst A, from Figure 3 The spectrum shows that the sample has an obvious dual-channel structure, indicating that the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, wherein the micropore size is 0.45nm and the mesopore size is 3.4nm. The pores with a pore size of 0.45nm are provided by the ZRP-5 molecular sieve, and the pores with a pore size of 3.4nm are provided by the HMS all-silicon mesoporous molecular sieve.
[0085] (2) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0086] The performance of the catalyst in the catalytic cracking reaction of waste plastics was evaluated in a fixed bed reactor. The catalyst loading was 10.0 g, the loading amount of waste polyethylene plastic particles was 50.0 g, the reaction temperature was 500 ° C, the reaction pressure was 0.1 MPa, the reaction time was 1 hour, and the product was cooled and the gas-liquid separation was performed. The gas composition was calculated by using a fixed bed reactor equipped with Al 2 O 3 -S capillary column and hydrogen flame detector (FID) Agilent 6890 gas chromatograph analysis, using programmed temperature, correction factor for quantitative analysis; liquid composition is analyzed by Agilent 6890 gas chromatograph equipped with PONA column. The reaction results are shown in Table 1.
[0087] Example 2
[0088] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0089] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0090] Dissolve 10.0g of hexadecylamine in a mixed solution of 30.0g of ethanol and 40.0g of distilled water, heat to 60°C, stir for 20 minutes, and then add 20.0g of methyl orthosilicate (TMOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 40 minutes. After the addition is complete, continue stirring and crystallizing at 60°C for 5 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with distilled water 10 times, filter after washing, and add distilled water to obtain 300g of HMS mesoporous molecular sieve slurry B.
[0091] 50 g ZRP-5A molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 70 and the specific surface area is 329m 2 / g, pore volume 0.16cm 3 / g) was added into a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the rotation speed of the grinding balls was 500r / min, and the ball milling time was 8h. 3.0g of the ZRP-5A molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for beating, the stirring speed was 300 rpm, and the beating time was 12h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 120°C for 3 hours and calcined at 500°C for 20 hours to obtain a microporous-mesoporous bi-porous composite catalyst B.
[0092] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst B, the content of the ZRP-5 molecular sieve is 30% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 70% by weight.
[0093] The specific surface area of the microporous-mesoporous composite catalyst B is 747 m 2 / g, pore volume 0.71cm 3 / g; and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal distribution, with a dual-channel structure, wherein the micropore diameter is 0.43nm and the mesopore diameter is 3.6nm.
[0094] The reaction performance of Catalyst B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0095] Example 3
[0096] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0097] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0098] Dissolve 10.0g of octadecylamine in a mixed solution of 150.0g of ethanol and 100.0g of distilled water, stir at 20°C for 1h, and then add 80.0g of butyl orthosilicate dropwise. Continue stirring during the addition, and the addition step lasts for 2h. After the addition is completed, continue stirring and crystallization at 20°C for 30 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with ethanol 5 times, filter it with suction, add distilled water, and obtain 500g of HMS mesoporous molecular sieve slurry C.
[0099] 50g ZRP-5C molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 300 and the specific surface area is 354m 2 / g, pore volume 0.20cm 3 / g) was added into a 300ml ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the rotation speed of the grinding balls was 300r / min, and the ball milling time was 24h. 9.3g of the ZRP-5C molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for slurrying, the stirring speed was 600 rpm, and the slurrying time was 6h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 60°C for 16 hours and calcined at 650°C for 6 hours to obtain a microporous-mesoporous bi-porous composite catalyst C.
[0100] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst C, the content of the ZRP-5 molecular sieve is 40% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 60% by weight.
[0101] The specific surface area of the microporous-mesoporous dual-pore composite catalyst C is 725 m 2 / g, pore volume 0.66cm 3 / g; and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal distribution, with a dual-channel structure, wherein the micropore diameter is 0.47nm and the mesopore diameter is 3.3nm.
[0102] The reaction performance of Catalyst C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0103] Example 4
[0104] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0105] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0106] Dissolve 10.0g of hexadecylamine in a mixed solution of 30.0g of ethanol and 40.0g of distilled water, heat to 60°C, stir for 20 minutes, and then add 20.0g of methyl orthosilicate (TMOS) dropwise. Continue stirring during the addition, and the addition step lasts for 40 minutes. After the addition is complete, continue stirring and crystallizing at 60°C for 5 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with distilled water 10 times, filter and add distilled water to obtain 400g of HMS mesoporous molecular sieve slurry D.
[0107] 50 g ZRP-5A molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 70 and the specific surface area is 329m 2 / g, pore volume 0.16cm 3 / g) was added into a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the rotation speed of the grinding balls was 500r / min, and the ball milling time was 8h. 2.4g of the ZRP-5A molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for beating, the stirring speed was 300 rpm, and the beating time was 12h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 120°C for 3 hours and calcined at 500°C for 20 hours to obtain a microporous-mesoporous bi-porous composite catalyst D.
[0108] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst D, the content of the ZRP-5 molecular sieve is 25% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 75% by weight.
[0109] The specific surface area of the microporous-mesoporous dual-pore composite catalyst D is 780 m 2 / g, pore volume 0.75cm 3 / g; the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal and has a dual-channel structure, wherein the micropore diameter is 0.43nm and the mesopore diameter is 3.5nm.
[0110] The reaction performance of Catalyst D was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0111] Example 5
[0112] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0113] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0114] Dissolve 10.0g of octadecylamine in a mixed solution of 150.0g of ethanol and 100.0g of distilled water, stir at 20°C for 1h, and then add 80.0g of butyl orthosilicate dropwise. Continue stirring during the addition, and the addition step lasts for 2h. After the addition is completed, continue stirring and crystallization at 20°C for 30 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with ethanol 5 times, filter it with suction, add distilled water, and obtain 600g of HMS mesoporous molecular sieve slurry E.
[0115] 50g ZRP-5C molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 300 and the specific surface area is 354m 2 / g, pore volume 0.20cm 3 / g) was added into a 300ml ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the rotation speed of the grinding balls was 300r / min, and the ball milling time was 24h. 11.0g of the ZRP-5C molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for slurrying, the stirring speed was 600 rpm, and the slurrying time was 6h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 60°C for 16 hours and calcined at 650°C for 6 hours to obtain a microporous-mesoporous bi-porous composite catalyst E.
[0116] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst E, the content of the ZRP-5 molecular sieve is 45% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 55% by weight.
[0117] The specific surface area of the microporous-mesoporous dual-pore composite catalyst E is 690 m 2 / g, pore volume 0.62cm 3 / g; and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal distribution, with a dual-channel structure, wherein the micropore diameter is 0.47nm and the mesopore diameter is 3.2nm.
[0118] The reaction performance of Catalyst E was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0119] Example 6
[0120] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0121] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0122] Dissolve 10.0g of hexadecylamine in a mixed solution of 30.0g of ethanol and 40.0g of distilled water, heat to 60°C, stir for 20 minutes, and then add 30.0g of tetraethyl orthosilicate (TEOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 40 minutes. After the addition is completed, continue stirring and crystallizing at 60°C for 5 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with distilled water 10 times, add distilled water after suction filtration, and obtain 500g of HMS mesoporous molecular sieve slurry F.
[0123] 50 g ZRP-5A molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 70 and the specific surface area is 329m 2 / g, pore volume 0.16cm 3 / g) was added into a 300ml ball mill, 8 agate grinding balls with a diameter of 2mm were placed, and ball milling was started. The temperature in the ball mill was controlled at 80°C, the rotation speed of the grinding balls was 500r / min, and the ball milling time was 8h. 2.0g of the ZRP-5A molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for beating, the stirring speed was 300 rpm, and the beating time was 12h to obtain a microporous-mesoporous dual-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous dual-porous composite catalyst slurry was dried at 120°C for 3 hours and calcined at 500°C for 20 hours to obtain a microporous-mesoporous dual-porous composite catalyst F.
[0124] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst F, the content of the ZRP-5 molecular sieve is 20% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 80% by weight.
[0125] The specific surface area of the microporous-mesoporous composite catalyst F is 800 m 2 / g, pore volume 0.79cm 3 / g; and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal distribution, with a dual-channel structure, wherein the micropore diameter is 0.43nm and the mesopore diameter is 3.5nm.
[0126] The reaction performance of Catalyst F was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0127] Example 7
[0128] This embodiment is intended to illustrate the microporous-mesoporous dual-porous composite catalyst prepared by the present invention and its application in the direct conversion of waste plastics to light olefins.
[0129] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0130] Dissolve 10.0g of octadecylamine in a mixed solution of 150.0g of ethanol and 100.0g of distilled water, stir at 20°C for 1h, and then add 60.0g of methyl orthosilicate dropwise. Continue stirring during the addition, and the addition step lasts for 2h. After the addition is completed, continue stirring and crystallizing at 20°C for 30 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with ethanol 5 times, filter it with suction, add distilled water, and obtain 400g of HMS mesoporous molecular sieve slurry G.
[0131] 50g ZRP-5C molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 300 and the specific surface area is 354m 2 / g, pore volume 0.20cm 3 / g) was added into a 300ml ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the rotation speed of the grinding balls was 300r / min, and the ball milling time was 24h. 20.0g of the ZRP-5C molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for slurrying, the stirring speed was 600 rpm, and the slurrying time was 6h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 60°C for 16 hours and calcined at 650°C for 6 hours to obtain a microporous-mesoporous bi-porous composite catalyst G.
[0132] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst G, the content of the ZRP-5 molecular sieve is 50% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 50% by weight.
[0133] The specific surface area of the microporous-mesoporous dual-pore composite catalyst G is 650 m2 / g, pore volume 0.58cm 3 / g; and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal distribution, with a dual-channel structure, wherein the micropore diameter is 0.47nm and the mesopore diameter is 3.8nm.
[0134] The reaction performance of Catalyst G was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0135] Comparative Example 1
[0136] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0137] Dissolve 10.0g of hexadecylamine in a mixed solution of 30.0g of ethanol and 40.0g of distilled water, heat to 60°C, stir for 20 minutes, and then add 20.0g of methyl orthosilicate (TMOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 40 minutes. After the addition is completed, continue stirring and crystallizing at 60°C for 5 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with distilled water 10 times, filter and add distilled water to obtain 300g of HMS mesoporous molecular sieve slurry D1.
[0138] 50 g ZRP-5A molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 70 and the specific surface area is 329m 2 / g, pore volume 0.16cm 3 / g) was added into a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the rotation speed of the grinding balls was 500r / min, and the ball milling time was 8h. 0.8g of the ZRP-5A molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for beating, the stirring speed was 300 rpm, and the beating time was 12h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 120°C for 3 hours and calcined at 500°C for 20 hours to obtain a microporous-mesoporous bi-porous composite catalyst D1.
[0139] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst D1, the content of the ZRP-5 molecular sieve is 10% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 90% by weight.
[0140] The specific surface area of the microporous-mesoporous dual-pore composite catalyst D1 is 953 m 2 / g, pore volume 0.94cm3 / g, and the double-channel pore sizes are 0.43nm and 3.6nm respectively.
[0141] The reaction performance of catalyst D1 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0142] Comparative Example 2
[0143] (1) Preparation of microporous-mesoporous dual-porous composite catalysts
[0144] Dissolve 10.0g of octadecylamine in a mixed solution of 150.0g of ethanol and 100.0g of distilled water, stir at 20°C for 1h, and then add 80.0g of butyl orthosilicate dropwise. Continue stirring during the addition, and the addition step lasts for 2h. After the addition is completed, continue stirring and crystallization at 20°C for 30 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product with ethanol 5 times, filter it with suction, add distilled water, and obtain 600g of HMS mesoporous molecular sieve slurry D2.
[0145] 50g ZRP-5C molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 300 and the specific surface area is 354m 2 / g, pore volume 0.20cm 3 / g) was added into a 300ml ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the rotation speed of the grinding balls was 300r / min, and the ball milling time was 24h. 54.0g of the ZRP-5C molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for slurrying, the stirring speed was 600 rpm, and the slurrying time was 6h to obtain a microporous-mesoporous bi-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous bi-porous composite catalyst slurry was dried at 60°C for 16 hours and calcined at 650°C for 6 hours to obtain a microporous-mesoporous bi-porous composite catalyst D2.
[0146] Wherein, based on the total weight of the microporous-mesoporous dual-porous composite catalyst D2, the content of the ZRP-5 molecular sieve is 80% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 20% by weight.
[0147] The specific surface area of the microporous-mesoporous dual-pore composite catalyst D2 is 478 m 2 / g, pore volume 0.35cm 3 / g, and the double-channel pore sizes are 0.47nm and 3.3nm respectively.
[0148] The reaction performance of catalyst D2 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0149] Comparative Example 3
[0150] The cracking catalyst was prepared in the same manner as in Example 1, except that:
[0151] Step (1) in Example 1 was eliminated, and only ZRP-5 molecular sieve was used as the cracking catalyst without adding HMS all-silica mesoporous molecular sieve.
[0152] The reaction performance of ZRP-5B molecular sieve was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0153] Comparative Example 4
[0154] The cracking catalyst was prepared in the same manner as in Example 1, except that:
[0155] The cracking catalyst was prepared according to the method of step (1) in Example 1, except that the preparation conditions were changed, and ZRP-5 molecular sieve was not used, and only HMS mesoporous molecular sieve was used. The specific process is as follows:
[0156] Dissolve 10.0g of dodecylamine in a mixed solution of 72.0g of ethanol and 63.0g of distilled water, heat to 40°C, stir for 30 minutes, and then add 42.0g of tetraethyl orthosilicate (TEOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 2h. After the addition is completed, continue stirring and crystallizing at 40°C for 20 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtering, wash the solid product 8 times with anhydrous ethanol, dry at 90°C for 5 hours, and calcine at 600°C for 12 hours to obtain 11.5g of HMS all-silica mesoporous molecular sieve A.
[0157] The specific surface area of HMS all-silica mesoporous molecular sieve A is 1021m 2 / g, pore volume 1.02cm 3 / g.
[0158] The reaction performance of HMS all-silica mesoporous molecular sieve A was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0159] Comparative Example 5
[0160] The cracking catalyst was prepared in the same manner as in Example 1, except that:
[0161] The ball milling process of ZRP-5B molecular sieve in step (1) of Example 1 and the slurrying process in catalyst preparation were eliminated, and 3.5 g of ZRP-5B molecular sieve was directly mixed with 6.5 g of HMS all-silica mesoporous molecular sieve A to obtain catalyst D3.
[0162] The reaction performance of catalyst D3 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0163] Comparative Example 6
[0164] The cracking catalyst was prepared in the same manner as in Example 1, except that:
[0165] The HMS all-silicon mesoporous molecular sieve was replaced with commercially available silica powder, and a microporous-mesoporous dual-porous composite catalyst was prepared by ball milling. The specific process is as follows:
[0166] 18 g ZRP-5B molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 100 and the specific surface area is 342m 2 / g, pore volume 0.18cm 3 / g) and 32g of commercially available silicon dioxide powder (specific surface area 274m 2 / g, pore volume 0.54cm 3 / g) was added into a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed in the ball mill to start ball milling. The temperature in the ball mill was controlled at 60°C, the speed of the grinding balls was 400r / min, and the ball milling time was 16h to obtain a microporous-mesoporous dual-porous composite catalyst D4.
[0167] Based on the total weight of the catalyst D4, the content of the ZRP-5 molecular sieve was 36% by weight, and the content of the silicon dioxide was 64% by weight.
[0168] The specific surface area of catalyst D4 is 296m 2 / g, pore volume 0.40cm 3 / g, and the double-channel pore sizes are 0.45nm and 17nm respectively.
[0169] The reaction performance of catalyst D4 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0170] Comparative Example 7
[0171] The cracking catalyst was prepared in the same manner as in Example 1, except that:
[0172] The microporous-mesoporous dual-porous composite catalyst D5 was prepared according to the method of step (1) in Example 1.
[0173] The difference is that the ZRP-5B molecular sieve is replaced with the ZSM-5 molecular sieve. The specific process is as follows:
[0174] Dissolve 10.0g of dodecylamine in a mixed solution of 72.0g of ethanol and 63.0g of distilled water, heat to 40°C, stir for 30 minutes, and then add 42.0g of tetraethyl orthosilicate (TEOS) dropwise. Continue stirring during the addition process, and the addition step lasts for 2h. After the addition is complete, continue stirring and crystallizing at 40°C for 20 hours. After the crystallization is completed, separate the solid product from the mother liquor by filtration, wash the solid product 8 times with anhydrous ethanol, filter it with suction, add distilled water, and obtain 400g of HMS mesoporous molecular sieve slurry A.
[0175] 50g ZSM-5 molecular sieve (SiO 2 / Al 2 O 3 The molar ratio is 25 and the specific surface area is 337m 2 / g, pore volume 0.27cm 3 / g) was added into a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 60°C, the rotation speed of the grinding balls was 400r / min, and the ball milling time was 16h. 6.2g of the ZSM-5 molecular sieve powder obtained after ball milling was added to the HMS all-silicon mesoporous molecular sieve slurry for slurrying, the stirring speed was 500 rpm, and the slurrying time was 10h to obtain a microporous-mesoporous dual-porous composite catalyst slurry. The white solid obtained by suction filtration of the microporous-mesoporous dual-porous composite catalyst slurry was dried at 90°C for 5 hours and calcined at 600°C for 12 hours to obtain a microporous-mesoporous dual-porous composite catalyst D5.
[0176] Based on the total weight of the catalyst D5, the content of the ZSM-5 molecular sieve is 36% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 64% by weight.
[0177] The reaction performance of catalyst D5 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0178] The reaction performance of catalyst D5 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (2) of Example 1. The evaluation results are listed in Table 1.
[0179] Table 1
[0180]
[0181]
[0182] It can be seen from the above results that the microporous-mesoporous dual-porous composite catalyst provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins is high.
[0183] In Comparative Example 1, the content of HMS all-silicon mesoporous molecular sieve is too high and the content of ZRP-5 molecular sieve is too low. Due to the small number of acidic centers on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.
[0184] In Comparative Example 2, the content of HMS all-silicon mesoporous molecular sieve is too low, and the content of ZRP-5 molecular sieve is too high. Due to the small number of mesoporous channels in the catalyst, the diffusion of reactant and product molecules is hindered during the reaction, resulting in a low yield of light olefins.
[0185] In Comparative Example 3, only ZRP-5 molecular sieve was used as the cracking catalyst, and HMS all-silicon mesoporous molecular sieve was not added. Since the catalyst did not contain mesoporous channels, the diffusion of reactant and product molecules was hindered during the reaction, resulting in a low yield of light olefins.
[0186] In Comparative Example 4, only HMS all-silicon mesoporous molecular sieve was used as the cracking catalyst, and ZRP-5 molecular sieve was not added. Since there were almost no active acidic centers on the catalyst, the raw material conversion rate and the yield of light olefins were low.
[0187] In Comparative Example 5, the ball milling process of ZRP-5 molecular sieve and the slurrying process in catalyst preparation were eliminated, and ZRP-5 molecular sieve was directly mixed with HMS all-silicon mesoporous molecular sieve. Since the microporous molecular sieve with acidic center and the HMS molecular sieve with mesoporous structure were not mixed uniformly, the yield of light olefins was low.
[0188] In Comparative Example 6, commercially available silica powder was used to replace the HMS all-silicon mesoporous molecular sieve. Since the mesoporous channel structure of the commercially available silica was irregular, the yield of light olefins was low.
[0189] In Comparative Example 7, SiO 2 / Al 2 O 3 The ZSM-5 molecular sieve with a molar ratio of 25 replaced the ZRP-5 molecular sieve. Since the acid center of the ZSM-5 molecular sieve has a greater acidity strength, more reaction by-products are produced and the yield of light olefins is lower.
[0190] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A microporous-mesoporous dual-porous composite catalyst, characterized in that: The microporous-mesoporous dual-pore composite catalyst comprises a ZRP-5 molecular sieve and an HMS all-silicon mesoporous molecular sieve, and the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, with a micropore size of 0.3-0.6 nm and a mesopore size of 2-5 nm; Based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 20-50% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 50-80% by weight.
2. The microporous-mesoporous dual-pore composite catalyst according to claim 1, wherein: The pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, with the micropore size being 0.4-0.5 nm and the mesopore size being 3-4 nm; Preferably, the pore size of the microporous-mesoporous dual-pore composite catalyst is bimodal, with the micropore size being 0.43-0.47 nm and the mesopore size being 3.2-3.8 nm.
3. The microporous-mesoporous dual-pore composite catalyst according to claim 1, wherein: Based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 25-45% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 55-75% by weight; Preferably, based on the total weight of the microporous-mesoporous dual-porous composite catalyst, the content of the ZRP-5 molecular sieve is 30-40% by weight, and the content of the HMS all-silicon mesoporous molecular sieve is 60-70% by weight.
4. The microporous-mesoporous dual-pore composite catalyst according to any one of claims 1 to 3, wherein: The SiO2 / Al2O3 molar ratio of the ZRP-5 molecular sieve is 70-300; Preferably, the ZRP-5 molecular sieve is selected from one or more of ZRP-5A molecular sieve, ZRP-5B molecular sieve and ZRP-5C molecular sieve.
5. The microporous-mesoporous dual-pore composite catalyst according to any one of claims 1 to 4, wherein: The specific surface area of the microporous-mesoporous dual-pore composite catalyst is 650-800m 2 / g, pore volume is 0.58-0.79ml / g; Preferably, the specific surface area of the microporous-mesoporous dual-pore composite catalyst is 690-780 m 2 / g, pore volume is 0.62-0.75ml / g; More preferably, the specific surface area of the microporous-mesoporous dual-pore composite catalyst is 725-776 m 2 / g, and the pore volume is 0.66-0.72ml / g.
6. A method for preparing a microporous-mesoporous dual-porous composite catalyst, characterized in that: The preparation method comprises: (I) ball-milling the ZRP-5 molecular sieve to obtain the ball-milled ZRP-5 molecular sieve; (II) mixing HMS all-silica mesoporous molecular sieve raw powder and water to obtain HMS all-silica mesoporous molecular sieve raw slurry; (III) contacting the ball-milled ZRP-5 molecular sieve and the HMS all-silica mesoporous molecular sieve slurry and performing a slurry treatment to obtain a microporous-mesoporous dual-porous composite catalyst slurry; (IV) The microporous-mesoporous dual-porous composite catalyst slurry is filtered, dried and calcined to obtain a microporous-mesoporous dual-porous composite catalyst.
7. The preparation method according to claim 6, wherein: The ball milling conditions include: the speed of the grinding balls is 200-600 r / min, the temperature in the ball mill is 30-90° C., and the ball milling time is 5-50 h; And / or, the beating conditions include: stirring speed ≥ 100 rpm, preferably ≥ 300 rpm; stirring time can be 1-24h, preferably 5-12h; And / or, the weight ratio of the ZRP-5 molecular sieve to the HMS all-silica mesoporous molecular sieve slurry is 1:(20-250), preferably 1:(50-180).
8. The preparation method according to claim 6, wherein: The method for preparing the HMS all-silicon mesoporous molecular sieve raw powder comprises: (1) mixing and contacting a template, an alcohol and water under hydrolysis gel making conditions to obtain a mixture; wherein the template is a neutral surfactant; (2) adding a silicon source dropwise to the mixture to obtain a gel mixture; (3) crystallizing the gel mixture; and then filtering and washing the crystallized product to obtain HMS all-silica mesoporous molecular sieve raw powder.
9. The preparation method according to claim 8, wherein: The template agent is selected from one or more of dodecylamine, tetradecylamine, hexadecylamine and octadecylamine; and / or, the alcohol is ethanol; And / or, the silicon source is a silicon-containing organic compound and / or a silicon-containing inorganic compound, preferably a silicon-containing organic compound, more preferably one or more of ethyl orthosilicate, methyl orthosilicate and butyl orthosilicate.
10. The preparation method according to claim 8, wherein: The weight ratio of the template, the alcohol, the water and the silicon source is 1:(1-30):(2-20):(1-12); preferably 1:(3-15):(4-10):(2-8); And / or, the crystallization conditions include: temperature of 10-80° C. and time of 3-48 h.
11. A microporous-mesoporous dual-porous composite catalyst prepared by the preparation method according to claim 9 or 10.
12. Use of the microporous-mesoporous dual-porous composite catalyst according to any one of claims 1 to 8 and 11 in the direct catalytic cracking of waste plastics to produce light olefins.
13. The use according to claim 12, wherein: The application comprises: contacting the microporous-mesoporous dual-porous composite catalyst with particles of the waste plastic to react; And / or, the contact conditions include: temperature of 420-580°C, pressure of 0.01-1MPa, and contact time of 0.5-12h; And / or, the weight ratio of the microporous-mesoporous dual-porous composite catalyst to the waste polyethylene plastic particles is 1:(0.5-50).
Citation Information
Patent Citations
Use of a catalyst composition for the catalytic depolymerization of plastics waste
CN107949601A
Light gasoline cracking catalyst and preparation method thereof, and catalytic cracking method
CN111167504A
C4 olefin cracking yield-increasing propylene catalyst containing all-silicon mesoporous microspheres, and preparation method and application thereof
CN113304779A
Catalyst for preparing propylene and preparation method and application of catalyst
CN113731477A
Monomodal and polymodal catalyst supports and catalysts having narrow pore size distributions and their production
US5935897A
